Penerapan Model UTAUT Untuk Mengetahui Minat Dan Perilaku Dalam Transaksi Pembayaran Menggunakan Mobile Banking - Suginam, Suginam; Afriany, Joli; Sari, Dian Purnama; Wardayani, Wardayani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
Mobile Banking Channel or m banking is a facility provided by banks in the form of an application with various features to provide convenience in conducting financial transactions. One of the financial transaction features in addition to business needs is a non-business feature. This is to echo payments in the digital era as a banking commitment to support the steps of the government and stakeholders to increase public awareness to improve the economy. This study aims to test the influence of public interest and behavior on the interest and behavior of making payments using the m banking application online. This study uses a quantitative method, consisting of empirical data and obtained by filling out a questionnaire of 55 respondents from bank customers. The results of the study showed that performance expectancy, effort expectancy, facilitating conditions and social influence have a positive and significant influence on Use Behavior. Based on the results of the tests carried out, each P-Value of the variable is 0.000 which indicates that the P-Values ​​<0.05, therefore all hypotheses are accepted. That Performance Expectancy has a significant effect on Use Behavior, Effort expectancy has a significant effect on Use Behavior, Social influence has a significant effect on Use Behavior and Facilitating conditions have a significant effect on Use Behavior.